Extreme metabolic alkalosis with fludrocortisone therapy. Issue 694 (August 1983) - Burns, A.; Brown, T. M.; Semple, P.
Abstract : We present an unusual case of extreme metabolic alkalosis resulting from severe hypokalaemia caused by unmonitored fludrocortisone therapy. Biochemical aspects of the disorder are discussed, as is the successful treatment with diuretics and potassium replacement. Some dangers of this therapy and necessary precautions are emphasized.